Second report of RING finger protein 113A (RNF113A) involvement in a Mendelian disorder. Issue 3 (3rd December 2019) - Tessarech, Marine; Gorce, Magali; Boussion, Françoise; Bault, Jean‐Philippe; Triau, Stéphane; Charif, Majida; Khiaty, Salim; Delorme, Benoit; Guichet, Agnès; Ziegler, Alban; Bris, Céline; Laquerrière, Annie; et al.
Abstract: RING Finger Protein 113 A ( RNF113A, MIM 300951) is a highly conserved gene located on chromosome Xq24‐q25, encoding a protein containing two conserved zinc finger domains involved in DNA alkylation repair and premessenger RNA splicing. To date, only one pathogenic variant of RNF113A, namely c.901C>T; p.Gln301Ter, has been reported in humans by Tarpey et al. in 2009. Thereafter, Corbett et al. stated that this variant was responsible for an X‐linked form of nonphotosensitive trichothiodystrophy associated with profound intellectual disability, microcephaly, partial corpus callosum agenesis, microphallus, and absent or rudimentary testes. This variant was then shown to alter DNA alkylation repair, providing an additional argument supporting its pathogenicity and important clues about the underlying pathophysiology of nonphotosensitive trichothiodystrophy. Using exome sequencing, we identified exactly the same RNF113A variant in two fetuses affected with abnormalities similar to those previously reported by Corbett et al. To our knowledge, this is the second report of a RNF113A pathogenic variant in humans.